APPLYING METHODS OF CONSTRUCTIVIST PEDAGOGY IN THE TRAINING OF ENGINEERS. QUESTIONS OF METHODOLOGY IN DEVELOPING COURSE MATERIAL (PANGEEA, 2025)
In this article we point out a cutting edge method of teaching that is not very wide-spread as of today. We wish to draw attention to the fact that traditional methods are apt to fail when applied to students reaching higher education with greatly varying levels of existing background knowledge to build on. We need to find methods that can effectively grab the attention of students, inspires their creativity and involves them in the process of teaching/learning. For this end, we find the methods of constructivist pedagogy highly expedient. The range of possibilities can be further widened by applying features of web 2.0. Applicability of the methods is demonstrated through two examples, one from the field of basic courses, one from specialised studies.
Keywords: method of teaching; traditional methods; methods of constructivist pedagogy